Phase 2 trial of T-cell activation using MVI-816 and pembrolizumab in patients with metastatic, castration-resistant prostate cancer (mCRPC). Issue 3 (11th March 2022) - McNeel, Douglas G; Eickhoff, Jens C; Wargowski, Ellen; Johnson, Laura E; Kyriakopoulos, Christos E; Emamekhoo, Hamid; Lang, Joshua M; Brennan, Mary Jane; Liu, Glenn
Abstract : Background: We previously reported a trial using a DNA vaccine encoding prostatic acid phosphatase (MVI-816, pTVG-HP), given over 12 weeks concurrently or sequentially with pembrolizumab, in patients with mCRPC. We report the final analysis of this trial following two additional treatment arms in which patients with mCRPC continued concurrent treatment until progression. Materials and methods: Patients with mCRPC were treated with MVI-816 and pembrolizumab every 3 weeks (arm 3, n=20) or MVI-816 every 2 weeks and pembrolizumab every 4 weeks (arm 4, n=20). The primary objectives were safety, 6-month progression-free survival (PFS), median time to radiographic progression, and objective response rates. Secondary objectives included immunological evaluations. Results: In 25 patients with measurable disease, there were no complete response and one confirmed partial response in a patient who subsequently found to have an MSI hi tumor. 4/40 patients (10%) had a prostate-specific antigen decline >50%. The estimated overall radiographic PFS rate at 6 months was 47.2% (44.4% arm 3, 61.5% arm 4). Accounting for all off-study events, overall median time on treatment was 5.6 months (95% CI: 5.4 to 10.8 months), 5.6 months for arm 3 and 8.1 months for arm 4 (p=0.64). Thirty-two per cent of patients remained on trial beyond 6 months without progression. Median overall survival was 22.9 (95% CI: 16.2 to 25.6) months. One grade 4 event (hyperglycemia) was observed. Immune-related adverse events (irAEs) >grade 1 were observed in 42% of patients overall. Interferon-γ and/or granzyme B immune response to prostatic acid phosphatase was detected in 2/20 patients in arm 3 and 6/20 patients in arm 4. Plasma cytokines associated with immune activation and CD8+ T-cell recruitment were augmented at weeks 6 and 12. The development of irAE was significantly associated with a prolonged time on treatment (HR=0.42, p=0.003). Baseline DNA homologous recombination repair mutations were not associated with longer time to progression. Conclusions: Findings here demonstrate that combining programmed cell death 1 blockade with MVI-816 is safe, can augment tumor-specific T cells, and can result in a favorable 6-month disease control rate. Correlative studies suggest T-cell activation by vaccination is critical to the mechanism of action of this combination. Future randomized clinical trials are needed to validate these findings. Trial registration number: NCT02499835 .